1996
DOI: 10.1002/(sici)1097-0142(19960601)77:11<2339::aid-cncr24>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus infection in the neoplastic and nonneoplastic cells of lymphoid malignancies

Abstract: T-cell lymphomas contained EPCs more frequently than B-cell lymphomas. Nonneoplastic lymphocytes were infected with EBV more frequently than lymphoma cells. Rowe's latency II may be unstable in lymphoid malignancies. Some NHLs, especially T-cell lymphoma, may provide favorable conditions for EBV infection of nonneoplastic lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…4,5,10,11 Multiple studies have looked for the presence of EBV (i.e., EBER) in PTCL tumor tissue with variable results. [12][13][14][15][16][17][18][19][20][21][22][23][24] The incidence of EBV-associated PTCL differ substantially worldwide, 25 and studies focused on North American and European populations are limited. Some studies have suggested a worse survival in EBER1 PTCL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,10,11 Multiple studies have looked for the presence of EBV (i.e., EBER) in PTCL tumor tissue with variable results. [12][13][14][15][16][17][18][19][20][21][22][23][24] The incidence of EBV-associated PTCL differ substantially worldwide, 25 and studies focused on North American and European populations are limited. Some studies have suggested a worse survival in EBER1 PTCL.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have looked for the presence of EBV (i.e., EBER) in PTCL tumor tissue with variable results . The incidence of EBV‐associated PTCL differ substantially worldwide, and studies focused on North American and European populations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…2 Most EBV-related lymphomas are of a B-cell lineage; however, a subset of NK and T-cell lymphomas are also associated with EBV. 3,4 Specifically recognized B-cell lymphomas associated with EBV include classical Hodgkin lymphoma, Burkitt lymphoma, lymphomatoid granulomatosis, post transplant and other lymphoproliferative disorders associated with immunodeficiency, and subsets of diffuse large B-cell lymphoma. Large B-cell lymphomas associated with EBV are usually aggressive neoplasms and include several subtypes: plasmablastic lymphoma, diffuse large B-cell lymphoma associated with chronic inflammation, primary central nervous system lymphoma arising in immunosuppressed patients, and EBV-positive diffuse large B-cell lymphoma.…”
mentioning
confidence: 99%
“…The presence of LDH in the cell reflects an alteration in the metabolic pathways towards that of anaerobic glycolysis (Bloom et al, 1967;Pan et al, 1991), and its release from PBMC has been described but without detailed investigation in association with malignancies (Decker & Lohmann-Matthes, 1988;. As the greatest LDH release is observed in patients with HD, this might be linked to the association of HD with EBV, in Reed-Sternberg cells, and in a variable proportion of nonneoplastic lymphoid cells (Valente et al, 1994;Teramoto et al, 1996;Anagnostopoulous et al, 1996).…”
Section: Discussionmentioning
confidence: 99%